Polycyclic aromatic hydrocarbons (PAHs) and organochlorine pesticide residues in selected marine fish species along the coast of South Africa - Rufina-Mary Chinelo, Chukwumalume (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD (Food Sc))--Stellenbosch University, 2016.